THE RELATIONSHIP OF CLASS MANAGEMENT AND EDUCATOR EMOTIONAL INTELLIGENCE TO INCREASING TEACHING INTERESTS - Triani Adapari Marcella; Manahan P. Tampubolon; Mesta Limbong (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2021)
Increasing interest in teaching will have an impact on increasing students' interest in learning. Educators' interest as subjects and objects in the learning process is the key to success in achieving educational goals. The purpose of this study was to examine the relationship between classroom management and educators' emotional intelligence on increasing interest in teaching. There were 75 samples randomly selected from 79 educators at Saint Peter using the Hair et al. Method, from the number of indicators x 5. The method used was descriptive. quantitative. Data obtained from filling out a questionnaire of 20 statements from each variable, namely the class management variable (X1) there are 5 indicators, the teacher's emotional intelligence variable (X2) has 5 indicators, the teaching interest variable (Y) has 5 indicators. Data analysis techniques using simple correlation and multiple correlation. In the first hypothesis the results indicate a positive and significant relationship between class management and interest in teaching with a correlation coefficient of ry1 = 0.824 with a regression model Ŷ = 8,202 + 0.824 X1, tcount 15,354 is greater than t table = 1.992 and the coefficient of determination (R2) = 0.764 . The second hypothesis shows that there is a positive and significant relationship between the emotional intelligence of educators and the interest in teaching with the correlation coefficient ry2 = 0.443 with a regression model Ŷ = 31.691 + 0.443 X2, tcount 6.434 is greater than t table = 1.992 and the coefficient of determination (R2) = 0.362. The third hypothesis shows that there is a positive and significant relationship between classroom management and educators' emotional intelligence on teaching interest with a correlation coefficient of ry 1.2 = 0.823 with a regression model Ŷ = 6.817 + 0.758X1 + 0.086 X2, Fcount 122.082 is greater than Ftable = 3.124. Thus the classroom management and emotional intelligence variables of educators have a strong influence on increasing interest in teaching by 76.6% while the remaining 23.4% is influenced by other variables outside the research. Keywords: interest in teaching, classroom management, emotional intelligence